Interaction between balancing market design and market behaviour of wind power producers in China. (October 2020) - Wu, Zhaoyuan; Zhou, Ming; Li, Gengyin; Zhao, Tong; Zhang, Yan; Liu, Xiaojuan
Abstract: To fulfil a commitment to reduce greenhouse gas emissions, promoting renewable energy accommodation is a major goal in establishing a spot market in light of China's 2015 electricity market reform. Eight representative provinces with different power supply structures and generation portfolios carry out simulated operations as initial pilot spot markets. The balancing market, a significant section of the spot market that addresses fair transaction settlements to eliminate system imbalance in real time, is diverse among these pilot spot markets. Therefore, effective methodological support is needed to analyse the interaction between balancing market design and participant behaviour considering the market environment in China. Based on the incentive compatibility of the market design with the actual situation in China, this paper assigns wind power producers as market participants, since wind power integration aggravates real-time imbalances due to its natural uncertainty and fluctuation. This study first summarizes the key elements of balancing market design in China that exert great influence on wind power producers; then, an offering strategy model of wind power producers is proposed embedding into the balancing market clearing model to reveal the interactive effect between balancing market design and the behavioural decisions of market participants and to investigate the adequacy of the entire market. Using an example, the effects of key factors on market adequacy and wind power revenue are discussed, including the tolerance margin, programme time unit (PTU) duration, and imbalance pricing mechanism. Finally, corresponding recommendations for balancing market design in China are put forward. Highlights: A balancing market design evaluation model referring the reform in China is proposed. Interaction between balancing market design and behaviour of BRPs is analysed. A tolerance margin can lead to strategic offering of BRPs. The penalty factor is recommended to be higher on negative imbalances. The Programme Time Unit should be gradually shortened from 30 min to 5 min.